When the neighbors are noisy: effect of social challenge in collateral pens of stressed animals - Guevara, Raúl David; López-Vergé, Sergi; Pastor, Jose J.; Manteca, Xavier; Tedo, Gemma; Llonch, Pol (Frontiers in Veterinary Science, 2024)
Regrouping practices are frequent in pig production, altering hierarchy and triggering aggressive behaviors. The present study aimed to investigate the physiological responses of piglets to an experimental model designed to induce stress through systematic social mixing in two trials. In Trial A, a total of 144 crossbred piglets (25 days postweaning) housed in one room within 36 pens (four piglets/pen) were used and randomly assigned to either a control group (piglets maintained in their pen, Ctrl-A) or a social challenge group (piglets mixed, SC-A). In Trial B, the same number of animals (33 days postweaning) and crossbreed line was used, and each piglet was assigned either to a control group (Ctrl-B) or a social challenge group (SC-B) in two independent rooms (rooms Ctrl and SC, 12 pens/ room, six piglets/pen). The social challenge consisted of daily moves of three out of four pen mates and five out of six pen mates, for Trials A and B, respectively. In the Ctrl groups, all piglets stayed in their original pen. Before the 1st mixing day and at the end of the 3rd mixing day, saliva (cortisol concentration) and blood (cortisol concentration changes, hemogram, and immunologic activation) samples were collected from two random piglets per pen. Skin lesion scores of all piglets were also recorded on the front, middle, and rear body regions. In Trial A, the total skin lesions score was higher in the SC-A group compared to the Ctrl-A group after the social challenge (0.53 vs. 0.17; p < 0.05), but an unexpected increase between sampling days in the Ctrl-A piglets (0.06 vs. 0.17; p < 0.05) was also recorded, suggesting that Ctrl-A pigs showed similar aggressivity levels to the SC-A group. Hematological parameters hemoglobin, red blood cell counts, and leukocyte counts present similar changes in both treatment groups after the social challenge. Contrarily, in Trial B, the lesion score only increased in the piglets in room SC (0.08 vs. 0.34; p < 0.05). Results suggest that stable groups may show aggressive behaviors if they are in the same room with socially challenged pigs. Thus, the physical separation of treatment groups in social stress studies is recommended.